Restoration of elective spine surgery during the first wave of COVID-19: a UK-wide British Association of Spine Surgeons (BASS) prospective, multicentre, observational study. (23rd December 2021) - Mohammed, Riaz; Shah, Pranav; Durst, Alexander; Mathai, Naveen J.; Budu, Alexandru; Woodfield, Julie; Marjoram, Tom; Sewell, Matthew; ,
Abstract : Aims: With resumption of elective spine surgery services in the UK following the first wave of the COVID-19 pandemic, we conducted a multicentre British Association of Spine Surgeons (BASS) collaborative study to examine the complications and deaths due to COVID-19 at the recovery phase of the pandemic. The aim was to analyze the safety of elective spinal surgery during the pandemic. Methods: A prospective observational study was conducted from eight spinal centres for the first month of operating following restoration of elective spine surgery in each individual unit. Primary outcome measure was the 30-day postoperative COVID-19 infection rate. Secondary outcomes analyzed were the 30-day mortality rate, surgical adverse events, medical complications, and length of inpatient stay. Results: In all, 257 patients (128 males) with a median age of 54 years (2 to 88) formed the study cohort. The mean number of procedures performed from each unit was 32 (16 to 101), with 118 procedures (46%) done as category three prioritization level. The majority of patients (87%) were low-medium "risk stratification" category and the mean length of hospital stay was 5.2 days. None of the patients were diagnosed with COVID-19 infection, nor was there any mortality related to COVID-19 during the 30-day follow-up period, with 25 patients (10%) having been tested for symptoms. Overall, 32 patients (12%) developed a total of 34 complications, with the majority (19/34) being grade 1 to 2 Clavien-Dindo classification of surgical complications. No patient required postoperative care in an intensive care setting for any unexpected complication. Conclusion: This study shows that safe and effective planned spinal surgical services can be restored avoiding viral transmission, with diligent adherence to national guidelines and COVID-19-secure pathways tailored according to the resources of the individual spinal units. Cite this article: Bone Jt Open 2021;2(12):1096–1101.